Determinants of appointment nonattendance among outpatients with hidradenitis suppurativa - Britt Nilausen; Anne‐Liv Gerber; Nikolaj Holgersen; Valdemar W. Nielsen; Hans C. Ring; Simon F. Thomsen (Wiley, 2024)
Abstract Background Hidradenitis suppurativa (HS) is associated with several comorbidities and significant impairment of quality of life. Moderate to severe HS patients have often prolonged treatment courses at various hospitals. We investigated various factors that may be related to missed follow‐up visits during prolonged treatment courses among HS outpatients. Objectives To highlight potential predictors for appointment absenteeism among HS patients. Methods During a 12‐month period at a university hospital dermatology outpatient clinic, absenteeism and related factors were obtained for each visit at the hospital. Results Out of 161 unique follow‐up visits during a 12‐month period at a university hospital dermatology outpatient clinic, 37 patients (23.0%) were absentees. Patients with non‐attendance were more likely to be males (p = 0.02). Patients who were on biologic treatment for HS were less likely to miss appointments (p = 0.06). Conclusions Our study showed that almost one in four hospital outpatients with HS fail to show up for their scheduled appointments. The data suggest an increased awareness of high risk of missed follow‐up visits during treatment of HS patients.